A Review of Dietary Suggestions During COVID-19: Review Article (Journal of Pharma Insights and Research, 2024)
This review aims to focus on plant-based foods that improve immunity against COVID-19 in all age groups. The World Health Organization (WHO) has declared COVID-19 a global pandemic, and thousands of infections and deaths are being reported every day. This article reviews the properties of bioactive ingredients in foods and herbs to support the human immune system. Many traditional foods can boost immunity along with some antiviral effects. Using lots of vitamins C, D and E and bioactive ingredients like turmeric, ginger, cinnamon, garlic, neem, amla and probiotic yogurt, as well as minerals like zinc and magnesium, these foods can boost the immune response against COVID-19. In addition, certain dietary patterns, such as the Mediterranean diet, have been associated with improved immune function and reduced inflammation. In conclusion, a nutrient-rich diet featuring herbal products and specific vitamins and minerals plays a key role in improving the immune response against COVID-19